Identifying and Addressing Students’ Academic Procrastination In SMK N 3 Sampit During Covid-19 Pandemic Transition Period: A Guidance And Counseling Perspective - Riza Amalia Zaki; Agus Heriyanto; Maydana Izati; Noor Khalisah; Maidah Nur Faini (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
This study aimed to identify the relationship between academic procrastination and smartphone addiction, phubbing behavior, and self-control and to formulate an appropriate treatment to address procrastination following the identification result. This quantitative correlational study was conducted in  SMK Negeri 3 Sampit, involving 371 respondents recruited using a purposive sampling technique. The data were collected using four scales: Smartphone Addiction Scale (SAS), Generic Scale Of Phubbing, Self-control scale, and academic procrastination scale. Data were analyzed using product moment correlation and multiple linear regression. The result showed that smartphone addiction, phubbing, and self-control simultaneously and significantly relate to students’ academic procrastination by 42%, while the rest, 58%, was accounted for by other variables. Issues on academic procrastination could be treated using Cognitive Behavior therapy (CBT) with cognitive restructuring techniques and applying comprehensive guidance and counseling perspectives.